Indicadores financieros en el modelo de economía circular - Cobos Floriano, Sixta (2024)
Organizations need to produce products that are economically, socially,and environmentally balanced. The objective of the research was to validate the content of a Circular Economy (CE) measurement instrument for industrial organizations and contribute to sustainable development objectives. This was developed for a descriptive, non-experimental research. The content and relevance of the instrument was evaluated by six experts in the field. The result was a content validity ratio (CVR) of 1.00 as the highest and 0.20 as the lowest value, with an overall content validity index (CVI) of 0.75, which, according to the method used, the measurement instrument evaluated is admissible